The Effect of Quantum Teaching Method on Motivation and Arabic Language Learning Outcomes (Literature Study) - Azzahrah Istira Oktiva Pradini; Maman Abdurrahman; Mia Nurmala (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study analyzes the effectiveness of the Quantum Teaching method in improving motivation and learning outcomes in Arabic. Researchers use descriptive qualitative research methods with a systematic approach to conduct data analysis in a simplified approach. Data was collected through database search tools and literature search stages using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method. Article search strategies are carried out through international databases, such as Open Knowledge Maps, ResearchGate, and Google Scholar. The summary of this literature review is done using an analysis matrix. The results showed that applying the Quantum Teaching method significantly improved students' Arabic proficiency and learning outcomes. Quantum Teaching effectively improves student learning outcomes, motivation, and engagement. This method creates a comfortable, enjoyable learning environment and strengthens the interaction between teachers and students. In addition, Quantum Teaching also improves students' memory and learning potential.